INTERPRETATION OF ASSESSMENT RESULTS OF TEACHER’S ACTIVITY QUALITY OBTAINED THROUGH INFORMATION SERVICE KSUFEEDBACK FUNCTIONING - Spivakovsky О.В.; Alferova Л.М. (Journal of Information Technologies in Education (ITE), 2015)
This article presents the research results of the experience of information service KSU Feedback using in HEI to assess the quality of faculty staff teaching through students’ vision. Actual national and international scientific works and achievements that relate to our research are analyzed. Key theoretical and practical aspects of building a feedback circuit in high school are showcased.The principles, technical characteristics and requirements for effective feedback are considered. The results of the survey questions ranking is given by using simplified method of hierarchies’ analysis. The calculation example of the quantitative indicator of teacher’s activity effectiveness, which is based on results of an anonymous electronic targeting survey with taking into account the weights of each question, is given. The article includes a detailed analysis of the experience of information service’s KSU Feedback implementation in Kherson State University and in Zaporizhzhya National University. Phased concept of results interpretation which were obtained through the asessment of teacher’s activity quality by information service KSU Feedback using is disclosed. An overview analysis of the conflicts typology and approach of conflict situations solving with the help of conflict mapping method are given. The primary consistent patterns and trends whuch were obtained through experiment’s results and emerge in the process of feedback’s circuit building are hilighted.